2017
DOI: 10.1038/s41598-017-15586-0
|View full text |Cite
|
Sign up to set email alerts
|

FAM19A5, a brain-specific chemokine, inhibits RANKL-induced osteoclast formation through formyl peptide receptor 2

Abstract: Osteoclasts can be differentiated from bone marrow-derived macrophages (BMDM). They play a key role in bone resorption. Identifying novel molecules that can regulate osteoclastogenesis has been an important issue. In this study, we found that FAM19A5, a neurokine or brain-specific chemokine, strongly stimulated mouse BMDM, resulting in chemotactic migration and inhibition of RANKL-induced osteoclastogenesis. Expression levels of osteoclast-related genes such as RANK, TRAF6, OSCAR, TRAP, Blimp1, c-fos, and NFAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…,34 Accordingly, we have been suggested that WKYMVm, another FPR2 agonist, also suppresses osteoclastogenesis under both normal and inflammatory condition. In this study, we demonstrated that WKYMVm negatively regulates osteoclast…”
mentioning
confidence: 99%
“…,34 Accordingly, we have been suggested that WKYMVm, another FPR2 agonist, also suppresses osteoclastogenesis under both normal and inflammatory condition. In this study, we demonstrated that WKYMVm negatively regulates osteoclast…”
mentioning
confidence: 99%
“…Wang et al showed FAM19A5 inhibits the vascular smooth muscle cells proliferation and ameliorates neointima formation in the injured rat carotid arteries (8). Although several studies addressed contribution of FAM19A5 to neurological disorders (19)(20)(21)(22)(23), existing data on a relevant association of FAM19A5 and cardiac and metabolic disorders are very limited (8,9). To our knowledge, this is the first clinical observation pointing to the association of FAM19A5 with the pathogenesis of NAFLD.…”
Section: Introductionmentioning
confidence: 80%
“…Several studies have shown association of FAM19A5 gene with neurological and/or psychiatric diseases (19-22, 25, 26). FAM19A5 has been linked to in ammation, differentiation and cognition (19,21,23,26,27). But few studies have addressed the role of FAM19A5 in cardiometabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A intronic variant of FAM19A5 (family with sequence similarity 19 member A5) gene on 22q13.32 was also associated with an increased risk of pancreatic cancer (rs5768709). This gene encodes a TAFA protein expressed predominately in brain and may function as brain-specific chemokines or neurokines 198 . Prior to the ChinaPC study, there is no implication of PRLHR or FAM19A5 in the risk of pancreatic cancer and thus their susceptibility role is currently unknown.…”
Section: Common Low-risk Susceptibility Locimentioning
confidence: 99%